The audio frontier [computer audio engineers' retreat]. - Kushner, D. (IEEE spectrum)
Hardware and software engineers who work in the Wild West of computer audio gather annually at a Texas ranch to tackle their collective challenges, spend the nights in jam sessions, and commune with the emus. This paper describes the seventh annual Project Bar-B-Q, an offbeat and influential three-day retreat for leaders in the field of audio engineering. Their aim is to improve computer audio, and make consumers care more about computer audio in the first place. This long weekend is an opportunity for competitors to work together on divining the challenges that face them collectively.